Why is that Hammer in My Coffee? A Multimodal Imaging Investigation of Contextually Based Tool Understanding - Mizelle, J.C.; Wheaton, Lewis A. (Frontiers in Human Neuroscience, 2010)
Appropriate tool–object pairing is a natural part of our lives. When preparing to stir coffee, we know that a hammer is useful for some tasks but that it is not appropriate in this behavioral context. The neural correlates of this context–tool pairing process remain unclear. In the current work, we used event-related electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) to determine neural correlates for differentiating contextually correct and incorrect tool use. Subjects were shown images depicting correct (e.g., spoon used to stir coffee) or incorrect (e.g., hammer used to stir coffee) tool use. We identified distinct regional and temporal activations for identifying incorrect versus correct tool use. The posterior cingulate, insula, and superior temporal gyrus preferentially differentiated incorrect tool–object usage, while occipital, parietal, and frontal areas were active in identifying correct tool use. Source localized EEG analysis confirmed the fMRI data and showed phases of activation, where incorrect tool-use activation (0–200 ms) preceded occipitotemporal activation for correct tool use (300–400 ms). This work extends our previous findings to better identify the neural substrate for contextual evaluation of tool use, and may contribute to our understanding of neurological disorders resulting in tool-use deficits.